2013
DOI: 10.31729/jnma.2425
|View full text |Cite
|
Sign up to set email alerts
|

Left Axis Deviation in Electrocardiogram with Normal QRS Duration in Ambulatory Adults without Cardiac Symptoms: A Possible Marker of Glucose Intolerance

Abstract: Introduction: We are increasingly noticing isolated left axis deviation (LAD) in electrocardiogram in younger people with diabetes without obvious heart disease and association of LAD with glucose intolerance has not been explicitly raised before. We planned a study of ambulatory adults with borderline (0o to –30o) and moderate-to-marked (<–30o to –90o) LAD looking into their possible association with glucose intolerance with fasting plasma glucose (FPG) ≥100mg/dL. Methods: We consecutively enrolled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A few studies are focusing on blood glucose and ECG parameters but Paudyal et al on 100 participate, indicated a possible association between Impaired and left axis deviation. 34 Our negative association between FBS and QRS axis can indicate the same somehow but, this relationship was not significant. Another study reported a slight increase in PR interval in subjects with higher FBS.…”
Section: Each Metabolic Syndrome Component and Ecg Parametersmentioning
confidence: 69%
“…A few studies are focusing on blood glucose and ECG parameters but Paudyal et al on 100 participate, indicated a possible association between Impaired and left axis deviation. 34 Our negative association between FBS and QRS axis can indicate the same somehow but, this relationship was not significant. Another study reported a slight increase in PR interval in subjects with higher FBS.…”
Section: Each Metabolic Syndrome Component and Ecg Parametersmentioning
confidence: 69%
“…In a study of asymptomatic people aged 30 years or more not on any medication attending outdoor clinics for health checkup, the mean (SD) values of fasting plasma glucose are 101.0 ± 18.3 mg/dL in the slight left axis deviation group with QRS axis 0° to -30° (mean age 40.3 ± 8.5) and 122.9 ± 27.5 mg/dL in moderate-to-marked left axis deviation group with QRS axis -30° to -90° (mean age 54.5 ± 6.3). The frequency of glucose intolerance is 48.9% in the slight left axis deviation group with QRS axis 0° to -30° and 84.9% in moderate-to-marked left axis deviation group with QRS axis -30° to -90°, the difference being significant after conditioning the effects of age and sex (P ≤ 0.03) and after conditioning the effect of BP (P = 0.02) [44,45]. In a recent study with 85% of participants less than 55 years of age, left axis deviation was present in 8% of control group and 43.3% of type 2 diabetes [46].…”
Section: Left Axis Deviation and Glucose Intolerancementioning
confidence: 99%
“…It is now increasingly affecting the younger population [47]. The situation of the epidemic of diabetes could have led to observe and report the association of glucose intolerance and left axis deviation in relatively younger people more explicitly now [45,46].…”
Section: A Relatively New Phenomenonmentioning
confidence: 99%
“…equally applicable to such Infectious Diseases (ID) and NCDs, 21,27,28 as well as family planning and MCH including breastfeeding. For the implementation, from Paper to the Practice, of the guidelines of various vertical programmes, the leadership of well trained MDGPs in the Peripheral Health Services is essential(Figure 3).To meet now the grave challenge of NCDs especially hypertension, diabetes and resultant CVDs affecting relatively young active populations in the developing countries[31][32][33] the Peripheral Health Services will have to be strengthened 34 for the comprehensive, longitudinal healthcare of the people. Thus there appears two kinds of leadership required for the success…”
mentioning
confidence: 99%